Analysis on influence of self-fan cooling motor on fan aerodynamics - ZHU Lei; LIU Hanru; LI Linfeng; WANG Shiguang; ZHAO Yanchen; WANG Yangang (Xibei Gongye Daxue Xuebao, 2023)
With the development of multi electric/all electric aircraft, the degree of aircraft secondary energy electrification is becoming higher and higher. As the core component of the electrical system, the motor presents the trend of small volume and high-power density. The heat dissipation problem of compact motor is becoming more and more serious. At present, the self-driven fan cooling system is widely used in aircraft motors. In this paper, the axial fan cooling system of an aero generator is taken as the research object, and the changes of fan flow field and aerodynamic characteristics in the fan motor coupling model of the isolated fan and the installed motor are analyzed by using three-dimensional computational fluid simulation. At the same time, the influence of the change of the axial distance between the fan and the motor on the aerodynamic performance is also studied. The analysis of the simulation results shows that the close coupling between the motor and the fan components greatly affects the flow structure in the fan, resulting in the distortion potential effect on the fan outlet section. The fan flow field appears the blade root reflux, the channel vortex in the blade and the expansion of the corner separation area. With the increase of the axial distance between the motor and the fan, the influence of the motor on the flow in the fan gradually approaches the flow blocking effect.